Synaptic depression in the CA1 region of freely behaving mice is highly dependent on afferent stimulation parameters - Goh, Jinzhong J.; Manahan-Vaughan, Denise (Frontiers in Integrative Neuroscience, 2013)
Persistent synaptic plasticity has been subjected to intense study in the decades since it was first described. Occurring in the form of long-term potentiation (LTP) and long-term depression (LTD), it shares many cellular and molecular properties with hippocampus-dependent forms of persistent memory. Recent reports of both LTP and LTD occurring endogenously under specific learning conditions provide further support that these forms of synaptic plasticity may comprise the cellular correlates of memory. Most studies of synaptic plasticity are performed using in vitro or in vivo preparations where patterned electrical stimulation of afferent fibers is implemented to induce changes in synaptic strength. This strategy has proven very effective in inducing LTP, even under in vivo conditions. LTD in vivo has proven more elusive: although LTD occurs endogenously under specific learning conditions in both rats and mice, its induction in mice in the CA1 region has not been successfully demonstrated with afferent electrical stimulation alone. In this study we screened a large spectrum of protocols that are known to induce LTD either in hippocampal slices or in the intact rat hippocampus, to clarify if LTD can be induced by sole afferent stimulation in the mouse CA1 region in vivo. Low frequency stimulation at 1, 2, 3, 5, 7 or 10 Hz given in the range of 100 through 1800 pulses produced, at best, short-term depression that lasted for up to 60 min. Varying the administration pattern of the stimuli (e.g. 900 pulses given twice at 5 min intervals), or changing the stimulation intensity did not improve the persistency of synaptic depression. LTD that lasts for at least 24h occurs under learning conditions in mice. We conclude that a coincidence of factors, such as afferent activity together with neuromodulatory inputs, play a decisive role in the enablement of LTD under more naturalistic (e.g. learning) conditions.